Oral and perioral manifestations in Down's syndrome patients - S R Ashwinirani; Girish Suragimath (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Down syndrome (DS) is also known as trisomy 21, is a genetic disorder caused by defect in chromosome 21. It is the most commonly diagnosed congenital malformation/mental retardation syndrome. DS individuals have greater risk of many systemic conditions like epilepsy, diabetes, leukemia, hypothyroidism and upper respiratory tract infections. Advances in medical field have increased the mean survival rate of these individuals. The dentist should able to diagnose the oral manifestations in DS patients and improve the quality of life of these individuals. AIMS AND OBJECTIVES: The present study was designed to assess the oral and perioral features of DS patients and to compare age and gender wise distribution of these findings. MATERIALS AND METHODS: Total of 100 DS patients were included in the study from special school in western part of Maharashtra. The clinical examination was carried out to record perioral, intraoral hard and soft tissue features in a predesigned proforma. The frequency and percentage distribution of these features were compared between the gender and age groups. RESULTS: Out of 100 DS patients majority were males (63%). Fissured tongue was the most common (73%) intraoral feature present. Constricted palate was present in 59% of cases, Angles class III malocclusion was the most common occlusion abnormality present in these patients. CONCLUSION: Majority of patients affected with DS were males and fissured tongue was the most common soft tissue feature present in these individuals.